Cord blood T cell subpopulations and associations with maternal cadmium and arsenic exposures. - Unni C Nygaard; Zhigang Li; Thomas Palys; Brian Jackson; Melanie Subbiah; Meena Malipatlolla; Vanitha Sampath; Holden Maecker; Margaret R Karagas; Kari C Nadeau (PLoS ONE)
Background Arsenic and cadmium are environmental pollutants, and although the evidence for adverse immune effects after prenatal arsenic and cadmium exposures is increasing, little is known about the underlying immunological mechanisms. Methods We investigated the relationship between prenatal arsenic and cadmium exposures and a variety of T cell subpopulations measured in cord blood for 63 participants in the New Hampshire Birth Cohort Study. Post-partum toenail concentrations of arsenic and cadmium were used as an estimate of maternal exposure during pregnancy. The characteristics of cord blood proportions of T lymphocytes and subpopulations (expression of markers for Th1, Th2, Th17, Th1Th17, induced and natural regulatory T cells and NKTs) are presented. Results In regression analyses, maternal arsenic exposure levels were inversely associated with cord blood T helper memory cells (-21%, 95% CI: -36%, -3%) and the association was found to be stronger in females. They were also inversely associated with activated T helper memory cells, particularly in males (-26%, 95% CI: -43%, -3%). Similarly, inverse associations were observed between cadmium exposure levels and activated T helper memory cells (-16%, 95% CI: -30%, -1%) and also for T helper memory cells in females (-20%, 95% CI: -35%, -3%). Conclusion The results suggest that prenatal exposures to relatively low levels of arsenic and cadmium may contribute to altered distribution of T cell populations at birth. These changes in theory, could have contributed to the previously reported immunosuppressive effects observed later in infancy/childhood.